Mechanism of local anesthetic-induced disruption of raft-like ordered membrane domains - Kinoshita, Masanao; Chitose, Takeshi; Matsumori, Nobuaki (Biochimica et biophysica acta. General subjects, 2019)
Because ordered membrane domains, called lipid rafts, regulate activation of ion channels related to the nerve pulse, lipids rafts are thought to be a possible target for anesthetic molecules. To understand the mechanism of anesthetic action, we examined influence of representative local anesthetics (LAs); dibucaine, tetracaine, and lidocaine, on raft-like liquid-ordered (Lo)/non-raft-like liquid-disordered (Ld) phase separation. Impact of LAs on the phase separation was observed by fluorescent microscopy. LA-induced perturbation of the Lo and Ld membranes was examined by DPH anisotropy measurements. Incorporation of LAs to the membranes was examined by fluorescent anisotropy of LAs. The biding location of the LAs was indicated by small angle x-ray diffraction (SAXD). Fluorescent experiments showed that dibucaine eliminated the phase separation the most effectively, followed by tetracaine and lidocaine. The disruption of the phase separation can be explained by their disordering effects on the Lo membrane. SAXD and other experiments further suggested that dibucaine's most potent perturbation of the Lo membrane is attributable to its deeper immersion and bulky molecular structure. Tetracaine, albeit immersed in the Lo membrane as deeply as dibucaine, less perturbs the Lo membrane probably because of its smaller bulkiness. Lidocaine hardly reaches the hydrophobic region, resulting in the weakest Lo membrane perturbation. Dibcaine perturbs the Lo membrane the most effectively, followed by tetracaine and lidocaine. This ranking correlates with their anesthetic potency. This study suggests a possible mechanistic link between anesthetic action and perturbation of lipid rafts. [Display omitted] •Influence of local anesthetics on raft-like and non-raft-like domains was examined.•Dibucaine effectively perturbs the raft-like domains, followed by tetracaine.•Lidocaine shows the weakest influence on the raft-like membranes.•The anesthetic potency correlates with their propensity for domain perturbation.•Mechanistic link between disruption of lipid rafts and anesthetic action is indicated.